Effect of Nb addition on microstructural and mechanical properties of Ti-Nb based alloys produced by powder metallurgy - GÜLSOY, HAMİT ÖZKAN (PAMUKKALE UNIV, 2017)
Ti-Nb based alloys are promising materials in terms of material properties, such as biocompatibility, mechanical properties and corrosion resistance for human hard tissuse (such as bone) bio implant materials. Present study focused on the effects of Nb addition on the microstructure and mechanical properties of Ti-Nb binary alloy. For this purpose, pure Ti, Ti-16Nb, Ti-26Nb alloys were produced by conventional powder metallurgy (PM) method. Microstructural development and phase analysis of sintered samples were determined by using optical microscopy, SEM, EDS, XRD techniques. It was observed that microstructures of sintered Ti-Nb alloys consist of widmanstatten alpha+beta structure. With an increasing in the content of Nb (from 16 to 26 wt. %), the micro-hardness values of the alloys decrease from 430 HV to 327 HV, the bending strength of the alloys decreases from 1403 MPa to 1168 MPa and the elastic modulus of the alloys decreases from 103 GPa to 90 GPa. Also, it is worth noting that finer grains achieved and the amount of the beta-phase in the microstructure is increased with increasing Nb content Results of the experimental works showed that PM Ti-Nb alloys could be offered as candidate materials for clinical practice applications as an alternative to Ti-6Al-4V alloy.
Keywords: Biomedical Ti-Nb alloys; Powder metallurgy; Elastic modulus; Bio-implant material; TI-35NB ALLOY; CASTABILITY; PARAMETERS; IMPLANTS; POROSITY; MODULUS